2015
DOI: 10.1007/s11356-015-5086-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Crocin against zearalenone-induced oxidative stress in liver and kidney of Balb/c mice

Abstract: Zearalenone (ZEN) is a mycotoxin from Fusarium species commonly found in many food commodities and known to cause reproductive disorders. Several studies have shown that ZEN is hematotoxic and hepatotoxic and causes several alterations of immunological parameters. In the present study, we aimed to evaluate the protective effect of Crocin (CRO), a natural carotenoid, against ZEN-induced toxicity in both renal and hepatic tissues of Balb/c mice. We demonstrated that ZEN (40 mg/kg body weight (b.w.)) induced oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…(2012b) found feeding diets with ZEA (200 to 800 μg/kg) to weanling gilts decreased SOD and increased MDA in serum, while the addition of montmorillonite clay alleviated these adverse effects induced by ZEA. In the present study, significant interactions between toxins and MBA was observed in the serum antioxidant indices of pregnant gilts, besides, the addition of MBA counteracted the negative effects of ZEA on the antioxidant indices, suggesting that the disadvantageous effects of ZEA and the advantageous effects of MBA might be associated with the length of feeding period, the physiological status of animals, and even animal species and age ( Ben et al., 2015 ; Ren et al., 2016 ).…”
Section: Discussionsupporting
confidence: 53%
“…(2012b) found feeding diets with ZEA (200 to 800 μg/kg) to weanling gilts decreased SOD and increased MDA in serum, while the addition of montmorillonite clay alleviated these adverse effects induced by ZEA. In the present study, significant interactions between toxins and MBA was observed in the serum antioxidant indices of pregnant gilts, besides, the addition of MBA counteracted the negative effects of ZEA on the antioxidant indices, suggesting that the disadvantageous effects of ZEA and the advantageous effects of MBA might be associated with the length of feeding period, the physiological status of animals, and even animal species and age ( Ben et al., 2015 ; Ren et al., 2016 ).…”
Section: Discussionsupporting
confidence: 53%
“…A great attention has been paid to the oxidative stress induced by Fusaria mycotoxins in the last decades. For example, dietary ZEA induced serious oxidative injuries in both renal and hepatic tissues in mice via adverse impact upon the level of the MDA, and the activities of CAT and SOD [ 37 ]. GSH-Px and SOD are the key antioxidant enzymes that can scavenge ROS generated from oxidant stress.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the administration of ZEN (10–30 mg/kg BW) for 4 weeks resulted in serum hormone changes and organ damage in mice [ 43 , 51 , 52 ]. In this study, all mice were free to eat and drink.…”
Section: Methodsmentioning
confidence: 99%